2021
DOI: 10.1021/acs.analchem.1c03822
|View full text |Cite
|
Sign up to set email alerts
|

Light-Driven Polarity Switching of the Chromatographic Stationary Phase with Photoreversibility

Abstract: Regrettably, conventional chromatographic columns have immutable polarity, resulting in requirements of at least two columns with polarity difference and sophisticated mechanical switching valves, which hinders the development of "micro-smart" multidimensional tandem chromatography. In this work, light-driven polarity switching was realized in a single capillary column based on the reversible trans−cis isomerization of 4-[3-(triethoxysilyl)propoxy]azobenzene as the stationary phase under light irradiation, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Applying these stimuli to a stationary phase, stimuli-responsive chromatographies have been developed. [9][10][11][12][13] The surface properties of a stimuli-responsive stationary phase can be adjusted by tuning these external stimuli. In the case of temperature-, and light-responsive chromatographies, the 'response' described above does not indicate a complete change in separation mode but rather a gradual change in polarity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Applying these stimuli to a stationary phase, stimuli-responsive chromatographies have been developed. [9][10][11][12][13] The surface properties of a stimuli-responsive stationary phase can be adjusted by tuning these external stimuli. In the case of temperature-, and light-responsive chromatographies, the 'response' described above does not indicate a complete change in separation mode but rather a gradual change in polarity.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to temperature- and light-responsive chromatography systems, pH switching is considered simpler in a conventional chromatography system. Light-irradiation systems are not available on conventional HPLC systems and can only be used on capillary columns, 9 as light cannot penetrate stainless-steel columns. Furthermore, temperature switching is possible with a conventional column oven; however, the temperature does not change rapidly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to their inherent properties, stimuli-responsive materials have been utilized to improve the extraction efficiencies of SPE devices for target analytes and develop new separation strategies. For example, Nagase et al examined the effect of the pore diameter (7, 12, and 30 nm) of silica beads on the elution behavior of analytes on a chromatographic column packed with a temperature-responsive copolymer hydrogel and observed temperature-dependent elution behaviors (retention times) owing to the temperature-responsive properties of the hydrogel and analyte diffusion into the bead pores . An et al realized light-driven polarity switching in a capillary gas chromatographic column based on the reversible trans – cis isomerization of the stationary phase under light irradiation and showed that this photosensitive column exhibited good polarity photoreversibility for high separation efficiency . However, stimuli-responsive materials have never been used to improve the (elution) peak profiles of target analytes.…”
Section: Introductionmentioning
confidence: 99%
“…Photoreversible color switching systems (PCSSs) that can reversibly change color between two states or isomers in response to physical and chemical stimuli, [1][2][3] have received growing attention in recent years owing to their practical applications in rewritable paper, color display, data storage, optoelectronic devices, and sensors. [4][5][6][7][8][9][10][11] Simultaneously, it can also be used in erasable and inkless printings as a promising solution to reduce the cost and environmental hazards arising from the usage of ink. [12][13][14] Significant efforts have been made to the development of organic and inorganic compounds with photoreversible color-switching properties.…”
Section: Introductionmentioning
confidence: 99%